Beberapa Karakteristik Umum Pertumbuhan Enam Kota Besar di Indonesia Tahun 1980 – 2000 - Asih Sriwinarti (Universitas Islam Indonesia, 2005)
Using six big city as analysis units, this research try to predict the pattern of the city growth in periode 1980 – 2000, in Indonesia. The analysis tool which used to see the city growth in primacy index. Beside that, this research also analyze some factors that influence city growth using panel data analysis.This research found (1) There was an inclination unbalance city growth in 1980 – 2000. From the year 1980 to the year 2000, Jakarta has been the city with the highest growth level. This condition is strengthen by a circumstance where Jakarta has entered highest transition level, which called the advanced urban transition. (2) Population, per capita income, and industrialization give positive impact to the city growth. (3) Educational degree and spillover effect from other regions give negative impact to the city growth.Key Words: Urban Growth, Index Primacy, Urban Transition